2.3 trillion spending bill includes COVID‐19 relief, adding 1.65 billion to SAPT BG. Issue 2 (9th January 2021) - Knopf, Alison
Abstract : Just before Christmas, Congress passed a 2.3 trillion spending package that included 1.4 trillion in appropriations for fiscal year 2021 and 900 billion for COVID‐19 relief (another "stimulus" bill). The appropriations bill level‐funded the Substance Abuse Prevention and Treatment block grant (SAPT BG) at 1.858 billion, and level‐funded the State Opioid Response (SOR) grant at 1.5 billion (this grant program includes stimulants as of last year). However, the COVID‐19 relief part of the law gave the SAPT BG an extra 1.65 billion for FY 2021.